INSPIRATIONAL LEADERSHIP, ORGANIZATIONAL CLIMATE, AND ORGANIZATIONAL SUPPORT AS PREDICTORS OF ORGANIZATIONAL COMMITMENT - Waluyo, Waris; Irawan, Irawan; Harinie, Luluk Tri; Meitina, Meitina (LPPM Universitas Jambi, 2026)
Organizational commitment is a critical determinant of effectiveness in high-risk institutions such as police organizations. However, existing studies largely examine leadership, organizational climate, and organizational support separately, with limited attention to the simultaneous mediating roles of organizational trust and work motivation. This study aims to analyze the influence of inspirational leadership, organizational climate, and organizational support on organizational commitment through organizational trust and work motivation. This study employed a quantitative explanatory design using a survey method. Data were collected from 215 active personnel of the B Pioneer Battalion of the Mobile Brigade Corps (Brimob), Central Kalimantan Regional Police, using purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that inspirational leadership, organizational climate, and organizational support do not directly affect organizational commitment. However, these variables significantly influence organizational trust and work motivation, which in turn significantly affect organizational commitment. Most mediation paths were significant, confirming the dominance of psychological mechanisms. The novelty of this study lies in integrating organizational and psychological antecedents simultaneously in a high-risk public sector setting. The findings imply that strengthening institutional trust and intrinsic motivation is more effective than relying solely on structural interventions to improve organizational commitment.